Prevalence of sleep pattern impairment post Covid-19 - Cruz-Romero , Joselyn Patricia; Chasillacta-Amores, Fabiola Beatriz (Sapienza: International Journal of Interdisciplinary Studies, 2023)
At the end of 2019, a pandemic brought remarkable variations in the corporal and cerebral health of individuals. The states of lockdown cause people and especially youngers vary their methods of connecting with people and studying. Stating that youth bring with emotional, cultural, and social variations, it is significant to recognize how this pandemic could further increase these states. Objective: Get to know the prevalence of post-COVID 19 sleep pattern deterioration in nursing students of Technical University of Ambato cohort October 2022 – March 2023. Methodology: Data was collected from a statistically sample of 275 students through an online questionnaire. Sociodemographic information was gathered and two instruments were used for validation: the insomnia severity index and the Epworth sleepiness scale. Results: It is shown that 83.64%of the individuals showed at least one mild sleep disturbance. 76.4% of the evaluated individuals presented some insomnia problems and 57.1% have sleepiness problems during the day. A statistically linked correlation was defined among the results of the two questionnaires and women have a slight tendency to experience sleepiness compared to men. Conclusion: The results and the information suggest that sleep disorders are generated by a poor framework of students ‘schedule. Despite this, lockdown may be a severe factor for the condition that could generate other disorders.